Association of Shifting Populations in the Root Zone Microbiome of Millet with Enhanced Crop Productivity in the Sahel Region (Africa) - Debenport, Spencer J. (Appl Environ Microbiol, 2015)
This study characterized specific changes in the millet root zone microbiome stimulated by long-term woody-shrub intercropping at different sites in Senegal. At the two study sites, intercropping with woody shrubs and shrub residue resulted in a significant increase in millet [Pennisetum glaucum (L.) R. Br.] yield (P < 0.05) and associated patterns of increased diversity in both bacterial and fungal communities in the root zone of the crop. Across four experiments, operational taxonomic units (OTUs) belonging to Chitinophaga were consistently significantly (P < 0.001) enriched in the intercropped samples, and “Candidatus Koribacter” was consistently significantly enriched in samples where millet was grown alone. Those OTUs belonging to Chitinophaga were enriched more than 30-fold in residue-amended samples and formed a distinct subgroup from all OTUs detected in the genus. Additionally, OTUs belonging to 8 fungal genera (Aspergillus, Coniella, Epicoccum, Fusarium, Gibberella, Lasiodiplodia, Penicillium, and Phoma) were significantly (P < 0.005) enriched in all experiments at all sites in intercropped samples. The OTUs of four genera (Epicoccum, Fusarium, Gibberella, and Haematonectria) were consistently enriched at sites where millet was grown alone. Those enriched OTUs in intercropped samples showed consistently large-magnitude differences, ranging from 30- to 1,000-fold increases in abundance. Consistently enriched OTUs in intercropped samples in the genera Aspergillus, Fusarium, and Penicillium also formed phylogenetically distinct subgroups. These results suggest that the intercropping system used here can influence the recruitment of potentially beneficial microorganisms to the root zone of millet and aid subsistence farmers in producing higher-yielding crops.